Enriching The Students’ Grammar Understanding by Analyzing the Sentences: The Third Semester Students at English Department Graha Nusantara University - Harahap, Rosni (Universitas Muhammadiyah Tapanuli Selatan, 2025)
Grammar is a core subject of writing skill in learning English language. Mastering grammar needs a lot of ways, technique or methods therefore, to all of English lectures or teachers should be able to teach it in easy and nice technique. Whereas, a researchers found in their classroom teaching there were more than 50% students are lack of grammar’s understanding in the English sentences. Although some of them understand about tenses in explanation, but most of them could not able to analyse when it was completed in the sentence. This research is focus on the understanding of grammar by analyzing the English sentences (simple sentence and compound sentence). The method used is classroom action research and the purpose of the research is to enrich the students’ understanding about grammar through the sentence analysis. The result of the research shows the improvement of students towards grammar. The pre-test result was 55 % students are lack of grammar understanding however after doing ten meetings for understanding grammar by analysing the sentences, the students’ improvement was raised to 85%. Teaching grammar is a challenging for the researchers themselves because there are so many students are not interested in learning it. Finally in the end of semester they were change their mind about grammar. Essentially, analyzing sentences is so attractive to do and able to improve their ability about grammar.